Implications of tissue specific STING protein flux and abundance on inflammation and the development of targeted therapeutics - Thomas E. Angel; Zhuo Chen; Ahmed Moghieb; Sze-Ling Ng; Allison M. Beal; Carol Capriotti; Leonard Azzarano; Debra Comroe; Michael Adam; Patrick Moore; Bao Hoang; Kelly Blough; et al. (PLoS ONE, 2025)
Drugs targeting the ER-resident innate immune receptor Stimulator of Interferon Genes (STING) are in development for treatments of cancer and inflammatory diseases. Accurate determination of STING receptor levels in normal and disease tissue is an essential component of modeling pharmacology and drug-target disposition. Using metabolic labeling with deuterium oxide paired with high resolution mass spectrometry, we report the protein fractional synthesis rates and turnover of STING in wild-type (C57BL/6) and inflamed mice carrying the Trex1 D18N mutation (Trex1D18N) as a STING-dependent model of human Acardi-Goutiéres syndrome. Remarkably, STING protein half-life is tissue specific with the shortest half-life of 4 days in colon and lymph node and longest half-life of 24 days in skeletal muscle. Despite the relative increase in STING protein abundance in the inflamed Trex1D18N mouse, the overall kinetics of protein degradation and resynthesis was similar between Trex1D18N and WT mice. The extent of tissue specific interferon stimulated gene transcription, a hallmark of SLE linked pathophysiology, correlates with the extend of increased STING levels in Trex1D18N tissues and appears inversely proportional to the turnover rate of STING. Understanding STING’s fractional protein synthesis rate and half-life provides a valuable component of quantitative modeling of drug pharmacology, dose frequency and targeting tissues of STING directed therapies.